The impact of balloon-expandable transcatheter aortic valve replacement on concomitant mitral regurgitation: a comprehensive computational analysis - Caballero, Andrés (J R Soc Interface, 2019)
The aortic and mitral valves function in a reciprocal interdependent fashion. However, the impact of transcatheter aortic valve replacement (TAVR) on the aortic–mitral continuity and severity of mitral regurgitation (MR) are poorly understood. In this study, a comprehensive engineering analysis was performed to investigate the impact of TAVR on MR severity and left heart dynamics in a retrospective patient case who harbours bicuspid aortic valve stenosis and concomitant functional MR. The TAVR procedure was computer simulated using a balloon-expandable valve, and the impact of three implantation heights on aortic–mitral coupling, MR severity and device performance were analysed. The accuracy and predictability of the computer modelling framework were validated with pre- and post-operative echo data. The highest deployment model resulted in higher stresses in the native leaflets, contact radial force and stent recoil, while the midway implantation model gave better haemodynamic performance and MR reduction in this patient case. Although the regurgitant volume decreased (less than 10%) for the three deployment configurations, no significant differences in MR severity improvement and mitral leaflet tethering were found. Acute improvement in MR was (i) due to the mechanical compression of the stent against the aortic–mitral curtain, (ii) due to an immediate drop in the ventricular pressure and transmitral pressure gradient. Albeit a single real clinical case, it is our hope that such detailed engineering computational analysis could shed light on the underlying biomechanical mechanisms of TAVR impact on MR.